Synthesis and characterization of alkaline earth and rare earth doped sialon Ceramics by spark plasma sintering. (June 2021) - Hakeem, Abbas Saeed; Khan, Majid; Ahmed, Bilal Anjum; Al Ghanim, Ahmed; Patel, Faheemuddin; Ehsan, Muhammad Ali; Ali, Sadaqat; Laoui, Tahar; Ali, Sharafat
Abstract: Several sialon ceramics compositions were synthesized by selecting metal oxides (MOs) in the nanosize range as additives in the oxynitride network. Nanosized precursors, including Si3 N4, SiO2, AlN, Al2 O3, and MO (MO = MgO, CaO, SrO, BaO, Y2 O3, La2 O3, CeO2, Nd2 O3, Eu2 O3, Dy2 O3, Er2 O3 and Yb2 O3, ) were used in the present study. Probe sonication and spark plasma sintering techniques were used for mixing the powder precursors and subsequent synthesis of sialon ceramics at a relatively low temperature of 1500 °C. Formation of α-sialon (general formula represented by Mm/v Si12-(m+n) Alm+n On N16-n ) was investigated for m and n values of 1.1 and 0.6, respectively and their structural, morphological, thermal, and mechanical properties were evaluated. The synthesized samples were characterized using X-ray diffractometry and field emission scanning electron microscopy to study the effect of the MOs on the microstructure and resulting densification, hardness, fracture toughness, thermal expansion and thermal conductivity. The sialon samples synthesized using the selected MOs exhibited similar relative densities in the range of 96 to 99% among all the samples and Vickers hardness (HV10 ) values, in the range of 15 to 20.8 GPa, depending on the type of MO. However, RE MOs exhibited a higher HV than AE MOs. Fracture toughness (KIc) was 4 MPa·m 1/2 for most of the samples, but the sample doped with Yb2 O3 had the highest KIc of 6.3 MPa·m 1/2 . The thermal conductivity decreased as the atomic number (atomic radii) of the AE increases and in the case of RE exhibited a random tendency. On the other hand, the thermal expansion coefficient increased with increasing atomic radii of the AE, and a mixed trend, with values in the range of 2.63 to 2.83 ppm·K −1, was observed for RE doped sialon ceramics. These behaviors are attributed to the resulting morphology and structure of alpha sialon comprised of both equiaxed and elongated grains. The properties of these sialon ceramics could be tailored by the proper selection of the suitable precursors and synthesis parameters. Graphical abstract: Unlabelled Image Highlights: Low-temperature synthesis of silaon utilizing nanosized precursors. Homogenization of starting powder precursors using ultrasonic probe sonication Synthesis of silaon using alkaline earth (AE) and rare earth (RE) metal oxides Study of structural and thermo-mechanical properties of AE and RE doped sialons